Dança e surdez: uma análise da produção de conhecimento acerca da pessoa surda a partir do sapateado - SOUSA, Hellen de Paula Santos (2022)
This monograph aimed to carry out an analysis of the production of knowledge about the deaf person from the tap dance. Being developed with 6 (six) deaf adults in the age group of 18 to 29 years of age. The methodology was qualitative based on action research, where the instruments of observation analysis and the five dynamics applied, which emerged from the project A Deafness and Pattaya: Neurological Study of Hearing Disorders and Development of Techniques and Teaching Strategies of Tapping for the Deaf. For a better understanding of this research, he discusses dialogues with authors such as: Alpendre (2008) who advocates deafness as a cultural difference and not as a disability, Garcia and Hass (2006) refer to dance as a universal language capable of providing benefits to its practitioners. The findings of the study show that the tap-to-deaf technique showed that knowing the body and its limits are important factors.